Convergent pathways in Parkinson’s disease - Cherubini, M; Wade-Martins, R (Springer Berlin Heidelberg, 2017)
Preferential degeneration of dopamine neurons (DAn) in the midbrain represents the principal hallmark of Parkinson's disease (PD). It has been hypothesized that major contributors to DAn vulnerability lie in their unique cellular physiology and architecture, which make them particularly susceptible to stress factors. Here, we report a concise overview of some of the cell mechanisms that may exacerbate DAn sensitivity and loss in PD. In particular, we highlight how defective protein sorting and clearance, endoplasmic reticulum stress, calcium dyshomeostasis and intracellular trafficking converge to contribute synergistically to neuronal dysfunction in PD pathogenesis.